1961
DOI: 10.3733/hilg.v31n14p459
|View full text |Cite
|
Sign up to set email alerts
|

The introduced purple scale parasite,Aphytis lepidosaphesCompere, and a method of integrating chemical with biological control

Abstract: be touched by the very maximum dosages." Also, Essig (1909) states: "The purple scale is considered the most serious of all our scale pests, as it is the most difficult to exterminate.... As yet, no natural parasite or predaceous insect has been found which will begin to cope with it." Lepidosaphes beckii is recorded as infesting a variety of plants in many of the locales where it occurs; however, it is rarely found on plants other than citrus in California. Purple scale thrives in areas having moderate temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Larvae of the Aphytis species studied tend to be gregarious, that is, more than one individual may develop per host. It has been shown that Aphytis lepidosaphes Compere usually lays 2 or more eggs per host and that 2 or more adult parasites usually emerge per host (DeBach and Landi, 1961). This commonly occurs also with A. melinus in the field.…”
Section: Species Having 1 Identical Ecological Nichesmentioning
confidence: 99%
“…Larvae of the Aphytis species studied tend to be gregarious, that is, more than one individual may develop per host. It has been shown that Aphytis lepidosaphes Compere usually lays 2 or more eggs per host and that 2 or more adult parasites usually emerge per host (DeBach and Landi, 1961). This commonly occurs also with A. melinus in the field.…”
Section: Species Having 1 Identical Ecological Nichesmentioning
confidence: 99%
“…Host-feeding, however, has been found to be the greatest cause of "unexplained" mortality in the black scale, S aisse tia oleae (Bern. ), the California red scale, Aonidiella a'urantii (Maskell), the purple scale, Lepidosaphes beckii (Newman}, andothers (De-Bach, 1943, 1969;DeBach and Landi, 1961). Tests were then devised to evaluate the host-feeding behavior of A. aonidiae.…”
Section: Host-feeding Behaviormentioning
confidence: 99%
“…Host-feeding or mutilation in the genus Aphytis has been recognized as important in the regulation of host population densities (DeBach and Landi, 1961;DeBach, 1969;Quednau, 1964). Quednau (1964) stated that "for an assessment of the utility of an Aphytis species for the biological control of scale pests, not only its fecundity is a factor, but also its controlling influence on the scales by host mutilation activities."…”
Section: Mortality Caused By Host-feeding On San Jose Scalementioning
confidence: 99%
“…However, autonomous entry (ecesis) occurred in many other places. In the Caribbean area, it has been collected in Puerto Rico, Jamaica, Guadaloupe and El Salvador (DeBaeh, 1971 ;DeBaeh & Landi, 1961 ;Rosen & DeBaeh, 1978, 1979. This is the 1 st time that A. lepidosaphes is reported in Costa Rica, but probably it is distributed in all Central American countries.…”
mentioning
confidence: 98%
“…The 1 St recorded success in biological control of L. beckii occurred in California, where A. lepidosaphes was introduced from China in 1948 and produced a substantial control (DeBaeh & Landi, 1961). Later, the wasp was carried from California to several countries around the world, but not to Costa Rica.…”
mentioning
confidence: 99%